Comparing of Bonding Failure Batten of Conventional and Self-etching Bonding Agents as Using in Orthodontic Brackets Bonding - علي, ديما; أحمد برهان, (Latakia University Journal -Medical Sciences Series, 2023)
Objective: The purpose of this vitro study was to investigate the amount of remnant adhesive which remains on the tooth surface after removal of metallic orthodontic brackets as using different generations of bonding agents by using Adhesive Remnant Index (ARI). Materials and Methods: 104 human premolars were used in this study. The premolar metallic brackets (Orthoclassic,USA) were bonded using four generations of bonding agents made in the same company (Ivoclar Vivadent) as following: Group (I) brackets were bonded by Tetric N-Bond ,Ivoclar Vivadent -5th generation,3 components 3 steps. Group (II) using (AdheSE ® LC,Ivoclar Vivadent)-6th generation, 2components 2 steps. Group (III) using (Multilink N-Prime A+B, Ivoclar Vivadent) -6th generation, 2 components 1 step. Group (IV) using (Tetric N-Bond self-Etch,Ivoclar Vivadent)-7th generation, 1 component 1 step. Then the brackets were debonded by applying shear strength (SS) using (Tinius Olsen ,H50KS,UK)device. The ARI was evaluated under stereomicroscope×10 magnification and using AutoCad 201. Results: According to the ARI evaluation, most of the failures involved the bracket/composite interface in groups (I ,IV) . But near to the tooth surface in the other two groups. Conclusion: The ARI scores indicate that using conventional bonding and self-etching bond of 7th generation are preferable to other generations.